Downregulation of TOP2 modulates neurodegeneration caused by GGGGCC expanded repeats. Issue 10 (22nd March 2021) - Jiao, Bin; Wang, Mengli; Feng, Hao; Bao, Han; Zhang, Feiran; Wu, Hao; Wang, Junling; Tang, Beisha; Jin, Peng; Shen, Lu
Abstract: GGGGCC repeats in a non-coding region of the C9orf72 gene have been identified as a major genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia. We previously showed that the GGGGCC expanded repeats alone were sufficient to cause neurodegeneration in Drosophila . Recent evidence indicates that GGGGCC expanded repeats can modify various gene transcriptomes. To determine the role of these genes in GGGGCC-mediated neurotoxicity, we screened an established Drosophila model expressing GGGGCC expanded repeats in this study. Our results showed that knockdown of the DNA topoisomerase II ( Top2 ) gene can specifically modulate GGGGCC-associated neurodegeneration of the eye. Furthermore, chemical inhibition of Top2 or siRNA-induced Top2 downregulation could alleviate the GGGGCC-mediated neurotoxicity in Drosophila assessed by eye neurodegeneration and locomotion impairment. By contrast, upregulated Top2 levels were detected in Drosophila strains, and moreover, TOP2A level was also upregulated in Neuro-2a cells expressing GGGGCC expanded repeats, as well as in the brains of Sod1 G93A model mice. This indicated that elevated levels of TOP2A may be involved in a pathway common to the pathophysiology of distinct ALS forms. Moreover, through RNA-sequencing, a total of 67 genes, involved in the pathways of intracellular signaling cascades, peripheral nervous system development, and others, were identified as potential targets of TOP2A to modulate GGGGCC-mediated neurodegeneration.